2003
DOI: 10.1159/000068070
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Second-Trimester Maternal Serum Inhibin A Levels in Asian Pregnancies with Fetal Down Syndrome and Other Chromosomal Abnormalities

Abstract: Subjects: To evaluate second-trimester maternal serum inhibin A levels in Asian pregnancies with fetal Down syndrome and other chromosomal abnormalities. Methods: Inhibin A level was measured from the serum samples of 25 chromosomally abnormal pregnancies, including 15 cases of Down syndrome, 4 cases of trisomy 18, 1 case of trisomy 13, and 5 cases of sex chromosome aneuploidies (4 cases of 47,XXY and 1 case of 45,X) and in a cohort of 150 controls during the second trimester of pregnancy. Results: The multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Other studies have reported similar results, that the median MoMs of the maternal serum quadruple test of normal Asian fetuses were higher than those of Western populations [ 17 19 ]. Thus, we recommend not using the WF model as a standard cutoff in quadruple screening for our and other Asian populations.…”
Section: Discussionsupporting
confidence: 61%
“…Other studies have reported similar results, that the median MoMs of the maternal serum quadruple test of normal Asian fetuses were higher than those of Western populations [ 17 19 ]. Thus, we recommend not using the WF model as a standard cutoff in quadruple screening for our and other Asian populations.…”
Section: Discussionsupporting
confidence: 61%
“…[46][47][48] There appears to be no consistent pattern in the serum markers for cases of trisomy 13, with the exception of a slight reduction in uE3 levels. 49 Levels of inhibin A were unaffected in one case of trisomy 13 studied by Hsu et al (0.89 MoM) 50 and four cases studied by Watanabe et al (1.14 MoM) 51 but were increased in six cases studied by Cuckle et al (2.22 MoM). 48 Further study of inhibin A levels in cases of trisomy 13 is needed.…”
Section: Inhibin-related Moleculesmentioning
confidence: 85%
“…54 Maternal serum inhibin A levels were increased (median ¼ 1.70 MoM) in one other sex chromosome abnormality, 47,XYY, studied. 50 Triploidy, or three copies of the haploid chromosome set, can originate from either maternal or paternal errors in meiosis. Type I triploidy results from an extra set of paternal chromosomes and is characterized by a large cystic placenta and fetal loss early in gestation.…”
Section: Inhibin a Levels In Other Fetal Abnormalitiesmentioning
confidence: 99%
“…We use as an example a meta-analysis on studies of inhibin-A as a screening marker for Down’s syndrome, which summarized the results of 20 studies. 425 Figure 1 shows this plot in a standard format. There is a vertical line designating no difference (ie.…”
mentioning
confidence: 99%